2010
DOI: 10.1007/s00404-010-1780-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive and integrated project to improve reproductive health at Oyam district, northern Uganda: insights from maternal death review at the district hospital

Abstract: Three main targets for future interventions were identified: improving the quality of assistance in the health centers, implementing an emergency room service in the hospital and counteract unsafe abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…From the screening and assessment of the grey literature and of the reference lists of relevant systematic reviews, a further 24 eligible publications were identified. From the total of 194 eligible publications18–211 included in our review (table 1; online supplementary appendix B), we captured 392 reported instances of infectious disease intervention delivery. Publication frequency varied since the beginning of the review study period in 1990, with peaks in 1996 and again in 2013 (n=26), and remaining high since then (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…From the screening and assessment of the grey literature and of the reference lists of relevant systematic reviews, a further 24 eligible publications were identified. From the total of 194 eligible publications18–211 included in our review (table 1; online supplementary appendix B), we captured 392 reported instances of infectious disease intervention delivery. Publication frequency varied since the beginning of the review study period in 1990, with peaks in 1996 and again in 2013 (n=26), and remaining high since then (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…A study of 17 maternal deaths in Uganda showed that 2 were due to meningitis. Both patients were HIV positive [16]. Menéndez et al [17] performed autopsies following 139 maternal deaths in Mozambique and found pyogenic meningitis in 7% of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Malaria was an important cause of maternal death in some studies,4345 while in others it was not as frequent 46. The substantial reduction in maternal mortality observed in Thailand after the implementation of early detection and treatment of malaria suggests that malaria is an important contributor to maternal mortality 47.…”
Section: Introductionmentioning
confidence: 99%